Use of innovative and communicative methods in teaching English (Eurasian Journal of Humanities and Social Sciences, 2022)
The introduction of information technologies into education will greatly diversify the process of information perception and processing. Thanks to the computer, the Internet and multimedia, a unique opportunity was created for students to absorb a large amount of information with further analysis and sorting. The motivational basis of educational activity is also expanding significantly. In the context of using multimedia, students get information from newspapers, television, conduct interviews and conduct teleconferences. It will be discussed about the use of innovative and communicative methods in teaching English.